Comparative Estimation of the Cytotoxic Activity of Different Parts of Cynara scolymus L.: Crude Extracts versus Green Synthesized Silver Nanoparticles with Apoptotic Investigation - Amgad I. M. Khedr; Abdelaziz F. S. Farrag; Ali M. Nasr; Shady A. Swidan; Mohamed S. Nafie; Maged S. Abdel-Kader; Marwa S. Goda; Jihan M. Badr; Reda F. A. Abdelhameed (MDPI AG, 2022)
Different parts of Cynara scolymus L. and their green synthesized eco-friendly silver nanoparticles (AgNPs) were screened for their cytotoxicity and apoptotic activity. Results showed that flower extract AgNPs exhibited more potent cytotoxicity compared to the normal form against PC-3 and A549 cell lines with IC50 values of 2.47 μg/mL and 1.35 μg/mL, respectively. The results were compared to doxorubicin (IC50 = 5.13 and 6.19 μg/mL, respectively). For apoptosis-induction, AgNPs prepared from the flower extract induced cell death by apoptosis by 41.34-fold change and induced necrotic cell death by 10.2-fold. Additionally, they induced total prostate apoptotic cell death by a 16.18-fold change, and it slightly induced necrotic cell death by 2.7-fold. Hence, green synthesized flower extract AgNPs exhibited cytotoxicity in A549 and PC-3 through apoptosis-induction in both cells. Consequently, synthesized AgNPs were further tested for apoptosis and increased gene and protein expression of pro-apoptotic markers while decreasing expression of anti-apoptotic genes. As a result, this formula may serve as a promising source for anti-cancer candidates. Finally, liquid chromatography combined with electrospray mass spectrometry (LC-ESI-MS) analysis was assessed to identify the common bioactive metabolites in crude extracts of stem, flower, and bract.